2013
DOI: 10.1063/1.4828999
|View full text |Cite
|
Sign up to set email alerts
|

Electrical characterization of defects introduced in n-Ge during electron beam deposition or exposure

Abstract: Articles you may be interested in Electron and hole deep levels related to Sb-mediated Ge quantum dots embedded in n-type Si, studied by deep level transient spectroscopy Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…Electron beam exposure (EBE) of the samples was achieved by using a 10 kV source (MDC model e-Vap 10CVS) with samples placed 50 cm away from the metal crucible as earlier reported by Auret et al [1] and Coelho et al [2]. The samples were exposed to EBE conditions for 50 minutes from a heated tungsten source using a beam current of 100 mA and an acceleration voltage of 10 kV [2]. This current was not enough to evaporate tungsten, but would have been sufficient to evaporate most other metals.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electron beam exposure (EBE) of the samples was achieved by using a 10 kV source (MDC model e-Vap 10CVS) with samples placed 50 cm away from the metal crucible as earlier reported by Auret et al [1] and Coelho et al [2]. The samples were exposed to EBE conditions for 50 minutes from a heated tungsten source using a beam current of 100 mA and an acceleration voltage of 10 kV [2]. This current was not enough to evaporate tungsten, but would have been sufficient to evaporate most other metals.…”
Section: Methodsmentioning
confidence: 99%
“…SBDs were fabricated in two stages: nickel Schottky contacts, 0.6 mm in diameter and of thickness 100 Å were first deposited by resistive evaporation technique before being quickly transferred into the electron beam deposition chamber for exposure to the electron beam. Electron beam exposure (EBE) of the samples was achieved by using a 10 kV source (MDC model e-Vap 10CVS) with samples placed 50 cm away from the metal crucible as earlier reported by Auret et al [1] and Coelho et al [2]. The samples were exposed to EBE conditions for 50 minutes from a heated tungsten source using a beam current of 100 mA and an acceleration voltage of 10 kV [2].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The epilayer was grown by chemical vapour deposition on the Si-face of the SiC substrate, which had a net doping density of 1×10 18 cm -3 and resistivity of 0.019 Ω-cm. The epilayer had a doping density of ~4×10 14 cm -3 .…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that metallization processes, such as electron-beam deposition and sputter deposition, introduce electrically active defects in measurable quantities at and close to M-S junction in conventional semiconductors such as Si, Ge and GaAs [15][16][17][18], and 6H-SiC [19]. The defects introduced influence the performance of devices and may alter the barrier height of metal-semiconductor contacts [20][21][22].…”
Section: Introductionmentioning
confidence: 99%